2014
DOI: 10.2967/jnumed.113.133843
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dosimetry of18F-FPEB in Humans

Abstract: 18 F-3-fluoro-5- [(pyridin-3-yl)ethynyl]benzonitrile ( 18 F-FPEB) is a potent and specific radioligand for the metabotropic glutamate receptor subtype 5 (mGluR5). Before undertaking clinical research studies with 18 F-FPEB, we performed studies of human radiation dosimetry. Methods: Serial whole-body scans were obtained in 9 healthy human subjects (5 men, 4 women) for 190-440 min after the intravenous administration of 18 F-FPEB. Radiation doses were estimated using the OLINDA/EXM software. Results: Peak organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Cumulated organ activity of the gall bladder might be overestimated, and of the large bowel underestimated, because it can be expected that tracer is cleared from small to large bowel within hours (Table 4 for results using ICRP 30 gastrointestinal model). Beyond that, organ doses in our study are in the same range as other lipophilic tracers [18]. The dosimetry results for [ 18 F]-PSS232 confirmed a low radiation dose to the urinary system (Table 3).…”
Section: Discussionsupporting
confidence: 70%
“…Cumulated organ activity of the gall bladder might be overestimated, and of the large bowel underestimated, because it can be expected that tracer is cleared from small to large bowel within hours (Table 4 for results using ICRP 30 gastrointestinal model). Beyond that, organ doses in our study are in the same range as other lipophilic tracers [18]. The dosimetry results for [ 18 F]-PSS232 confirmed a low radiation dose to the urinary system (Table 3).…”
Section: Discussionsupporting
confidence: 70%
“…According to the Radioactive Drug Research Committee guidelines in the United States, the effective dose for the whole body should not exceed 30 or 50 mSv/year (FDA 21 CFR 361.1). Previous studies have reported that the whole-body effect dose of PET scans used in the present study was 0.015-0.021 mSv/MBq (mean 0.018 mSv/MBq, Van Laere et al, 2010;Kessler et al, 2014;Sabri et al, 2015;Srinivasan et al, 2020). For an injected dose of 370 MBq, the whole-body was 6.68 mSv/each and 33.4 mSv/five study.…”
Section: Discussionmentioning
confidence: 49%
“…Clinical trials of mGluR 5 NAMs for FXS were limited by the variable age groups of study participants, problematic outcome measurements, placebo effects, and potentially the absence of a tool to measure the expression of mGluR 5 in the living brains of participants with FXS [2,[42][43][44]46,56,57]. Our finding that mGluR 5 expression measured by positron emission tomography (PET) with 3-[ 18 F]fluoro-5-(2-pyridinylethynyl)benzonitrile ([ 18 F]FPEB), a potent and safe specific mGluR 5 inhibitor (Figures 1 and 2) [58,59], is re-duced in all brain regions in men with FXS [2] compared to participants of both sexes with ASD and TD [2,42,[60][61][62], was confirmed utilizing positron emission tomography and magnetic resonance (PET/MR) imaging on an unmedicated cohort of older men with FXS and age-and sex-matched participants with TD suggesting that the current protocol may be a valuable biomarker for mGluR 5 expression in clinical trials of novel agents for humans with FXS and other subtypes of ASD [63]. We showed that [ 18 F]FPEB may be a promising tool to obtain quantitative measurements of mGluR 5 expression in individuals with FXS for clinical trials and other investigations [2,42,[64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%